Multi-element positive electrode material and preparation method thereof and lithium ion battery
By constructing a garnet-type and layered perovskite fast ion conductor cladding on the surface of the positive electrode material of the lithium-ion battery, the problems of poor crystal shape and weak binding force of the fast ion conductor are solved, and the electrochemical performance of the lithium-ion battery is improved and structural stability, achieving efficient lithium ion conduction and safety performance improvement.
Patent Information
- Application Number
- CN202210749118.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-06-28
AI Technical Summary
The fast ion conductors of the positive electrode materials of existing lithium-ion batteries have poor crystal shapes and weak binding force with multi-material materials, resulting in low lithium ion conduction rate and insufficient cycling stability and safety performance.
By constructing a garnet-type and layered perovskite-type fast ion conductor cladding on the surface of the multivariate positive electrode material, a lithium ion rapid transmission channel is formed, the interface impedance is reduced, and structural stability is improved through the dry coating process.
The discharge specific capacity, rate performance and cycle retention rate of lithium-ion batteries are improved, the safety performance is enhanced, the production process is simplified, and the cost is reduced.
Smart Images

Figure CN115188941B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a multi-element positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in consumer electronic devices. The rapid development of the new energy vehicle industry has put forward higher requirements for the energy density, safety, fast charging and discharging, and cycle life of power batteries. Nickel manganese cobalt oxide lithium positive electrode materials (referred to as multi-materials) have become the mainstream products of high-performance lithium-ion battery positive electrode materials. The specific capacity of multi-materials increases with the increase of nickel content and has received great attention. However, the cycle life, rate performance and safety performance of multi-materials deteriorate with the increase of nickel content.
[0003] The cathode material is usually modified by doping, coating and other means to meet the application requirements of industrialization. The common coating method is to form an inert coating layer on the surface of the multi-material matrix by sol-gel or mechanical mixing to alleviate the side reactions between the cathode material and the electrolyte, transition metal dissolution and other problems. In recent years, fast ion conductor coating of cathode materials has attracted extensive research. In the prior art, sol-gel or wet method is often used to coat the cathode material to form a fast ion conductor layer (Interface engineering on cathode side for solid garnet batteries, Chemical Engineering Journal, 2020, 387: 124089; CN 111755698). However, on the one hand, there is a large difference between the optimal temperature of fast ion conductor phase formation and the optimal temperature of cathode material coating. Therefore, the fast ion conductor generated in situ on the surface of the cathode material has a poor crystal form and a low lithium ion conduction rate, that is, no active lithium ion conduction surface coating layer is formed; on the other hand, the solvent used in the preparation process often destroys the crystal structure of the cathode material and reduces its cycle stability. In addition, there is also a dry coating method such as mechanical mixing without heat treatment (Surface modification of nickel-rich cathode materials by ionically conductive materials at room temperature, Energy Technology, 2021, 2100422) to form a coating layer on the multi-material. Due to the lack of heat treatment process, the chemical bonding force between the multi-material and the fast ion conductor is weak, and the effect is not obvious.
[0004] Therefore, it is of great significance to research and develop a positive electrode material with a fast ion conductor channel and low interface impedance on the surface. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems in the prior art that the fast ion conductor on the surface of the multi-material has poor crystal form, resulting in the inability to effectively conduct lithium ions, and the weak bonding force between the fast ion conductor and the multi-material, and to provide a multi-material positive electrode material and a preparation method thereof and a lithium ion battery. The fast ion conductor coated multi-material provided by the present invention can effectively improve the structural stability of the multi-material and reduce the interface impedance between the multi-material and the electrolyte through lattice and grain boundary modification and construction of lithium ion transmission channels on its surface, thereby improving the discharge specific capacity, rate performance, cycle retention rate and safety performance of the lithium ion battery.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a multi-element positive electrode material, wherein the multi-element positive electrode material comprises a substrate and a fast ion conductor coating layer coated on the surface of the substrate; the components of the fast ion conductor coating layer include Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and Li u J v La 2-w J' w O 4+ω ;
[0007] Among them, in the Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ wherein A is selected from at least one of Mg, Ca, Al and Ga, A′ is selected from at least one of Sr, Y and Ce, A″ is selected from at least one of Zn, Cu, Co, Ge, Hf, Ir, Mn, Mo, Ti, Ru, Se, Te, W, Sn, Sb, Nb and Ta, 0≤i≤2, 0≤j≤1, 0≤q≤2, 0≤δ≤1, and i, j, k are not all 0 at the same time;
[0008] Among them, in the Li u J v La 2-w J' w O 4+ω wherein J is selected from at least one of Al, Ni, Co, Mn, Cu and Fe, J' is selected from at least one of Ca, Ba, Sr, La, Y, Ce, Rb and Ru, 0<u≤1, 0<v≤1, 0≤w≤1, 0≤ω≤1.
[0009] A second aspect of the present invention provides a method for preparing a multi-element positive electrode material, wherein the preparation method comprises:
[0010] (1) preparing a mixed salt solution of cobalt salt, manganese salt and nickel salt according to the molar ratio of Ni:Co:Mn=(1-xy):x:y;
[0011] (2) contacting the mixed salt solution, the salt solution of the M source, the precipitant solution and the complexing agent solution to perform a coprecipitation reaction to obtain a solid-liquid mixed slurry; and then filtering, washing, drying and sieving the solid-liquid mixed slurry to obtain a multi-element positive electrode material precursor;
[0012] (3) mixing, sintering, crushing and screening the multi-element material precursor, the lithium source and the M' source compound to obtain a multi-element positive electrode material matrix;
[0013] (4) Using the first process: Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , Li u J v La 2-w J' w O 4+ω Mixing with the multi-element positive electrode material matrix, and subjecting to first sintering, crushing, and screening, to obtain a multi-element positive electrode material coated with a fast ion conductor;
[0014] or,
[0015] The second process: Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , lanthanum source, J source compound, J' source compound, lithium salt and the multi-element positive electrode material matrix are mixed, and after a second sintering, crushing and screening, a multi-element positive electrode material coated with a fast ion conductor is obtained.
[0016] The third aspect of the present invention provides a multi-element positive electrode material prepared by the aforementioned preparation method.
[0017] A fourth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the aforementioned multi-element positive electrode material as a positive electrode material.
[0018] Through the above technical solution, the present invention has the following advantages:
[0019] (1) In the present invention, a garnet-type fast ion conductor and a layered perovskite-type fast ion conductor coating layer are constructed on the multi-electrode positive electrode material through chemical bonds to form a lithium ion fast transmission channel, thereby increasing the electrochemical reaction rate at the interface, reducing the interface impedance, and improving the rate performance of the multi-electrode positive electrode material; the stable crystal structure of the coating layer itself can inhibit the side reaction between the multi-electrode positive electrode material and the electrolyte, that is, inhibit the increase of impedance during the cycle.
[0020] (2) In the present invention, while constructing a fast ion conductor coating layer on the surface of the multi-element positive electrode material, the ratio of lithium, nickel, cobalt and manganese components in the surface layer of the multi-element positive electrode material is changed to form a low-nickel shell layer, which helps to improve its structural stability and thermal stability.
[0021] (3) The present invention adopts a dry coating process to simultaneously form a garnet-type fast ion conductor and a layered perovskite-type fast ion conductor coating layer on the surface of the multi-electrode positive electrode material. The production and processing is easy, the cost is low, the pollution is extremely small, and it is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD patterns of the multi-component materials prepared in Comparative Example 1 and Example 1;
[0023] Figure 2 The first charge and discharge curves of the multi-element materials prepared in Comparative Example 1 and Example 1 in a liquid lithium battery;
[0024] Figure 3 This is a curve diagram of the cycle retention rate of the multi-material prepared in Comparative Example 1 and Example 1 in a liquid lithium battery. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] As mentioned above, the first aspect of the present invention provides a multi-element positive electrode material, wherein the multi-element positive electrode material comprises a substrate and a fast ion conductor coating layer coated on the surface of the substrate; the fast ion conductor coating layer comprises Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and Li u J v La 2-wJ' w O 4+ω ;
[0027] Among them, in the Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ wherein A is selected from at least one of Mg, Ca, Al and Ga, A′ is selected from at least one of Sr, Y and Ce, A″ is selected from at least one of Zn, Cu, Co, Ge, Hf, Ir, Mn, Mo, Ti, Ru, Se, Te, W, Sn, Sb, Nb and Ta, 0≤i≤2, 0≤j≤1, 0≤q≤2, 0≤δ≤1, and i, j, k are not all 0 at the same time;
[0028] Among them, in the Li u J v La 2-w J' w O 4+ω wherein J is selected from at least one of Al, Ni, Co, Mn, Cu and Fe, J' is selected from at least one of Ca, Ba, Sr, La, Y, Ce, Rb and Ru, 0<u≤1, 0<v≤1, 0≤w≤1, 0≤ω≤1.
[0029] The inventors of the present invention have discovered that: in the process of preparing multi-electrode positive electrode materials, by adopting a dry coating process, by controlling the sintering temperature, sintering rate and matching the corresponding coating agent, a suitable driving force for the coating reaction is provided, and a garnet-type fast ion conductor and a layered perovskite-type fast ion conductor coating layer are constructed on the surface of the multi-electrode positive electrode material through chemical bonds, forming a lithium ion fast transmission channel, increasing the electrochemical reaction rate at the interface, reducing the interface impedance, and improving the rate performance of the multi-electrode positive electrode material; the stable crystal structure of the coating layer itself can inhibit the side reaction between the multi-electrode positive electrode material and the electrolyte, that is, inhibiting the increase of impedance during the cycle process; in addition, while constructing the fast ion conductor coating layer on the surface of the multi-electrode positive electrode material, the proportion of lithium, nickel, cobalt and manganese components in the surface layer of the multi-electrode positive electrode material is changed to form a low-nickel shell layer, which helps to improve its structural stability and thermal stability.
[0030] According to the present invention, the components of the matrix include Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' βO2; wherein, M and M' are each independently selected from at least one of Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B; 0.9≤z≤1.3, 0.001≤x≤1, 0≤y≤1, 0<α≤0.1, 0<β≤0.1; preferably, M and M' are each independently selected from at least one of Al, Ba, Zr, Ti, Nb, Y, W, Sr, Cr, Mo, La, Ce, Mg and B; 1.0≤z≤1.1, 0.001≤x≤0.5, 0≤y≤0.5, 0<α≤0.05, 0<β≤0.05.
[0031] According to the present invention, the X-ray diffraction pattern (XRD) of the multi-element positive electrode material has, in addition to the characteristic peaks of the multi-element positive electrode material, Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and Li u J v La 2-w J' w O 4+ω At least one characteristic peak, its angle and corresponding crystal plane are shown in Table 1, wherein the characteristic peaks of the multi-element positive electrode material only list the three strongest peaks.
[0032] Table 1
[0033]
[0034] According to the present invention, the Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ Peak intensity I of (422) crystal plane (422) With Li u J v La 2-w J' w O 4+ω Peak intensity I of (103) crystal plane (103) The ratio is 0.2<I (422 / I (103) <1.5, preferably, 0.5 <I (422 / I (103) <1.2; Preferably, the Li 7-i A i La 3-jA' j Zr 2-q A” q O 12+δ (422) peak area A (422) With Li u J v La 2-w J' w O 4+ω Peak area A of (103) crystal face (103) The ratio is 1.0<A (422 / A (103) <5.0, preferably, 1.5<A (422) / A (103) <3.0.
[0035] According to the present invention, the Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ Peak intensity I of (422) crystal plane (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β The peak intensity of O2(003) crystal plane I (003) The ratio is 0.01%<I (422) / I (003) <1.2%, preferably, 0.1%<I (422) / I (003) <0.5%; preferably, the Li 7- i A i La 3-j A' j Zr 2-q A” q O 12+δ (422) peak area A (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β The peak area A of the O2(003) crystal plane (003) The ratio is 0.01%<A (422) / A(003) <1.2%, preferably, 0.1%<A (422) / A (003) <0.5%.
[0036] According to the present invention, preferably, A is selected from at least one of Al, and Ga, A' is selected from Sr and / or Ce; A" is selected from at least one of Co, Ti, W, Nb and Ta; 0≤i≤1, 0≤j≤0.5, 0≤q≤1, 0≤δ≤0.5.
[0037] According to the present invention, preferably, J is selected from at least one of Al, Ni, Co and Cu; J' is selected from at least one of Ba, Sr, Y and Ce; 0<u≤0.8, 0<v≤0.8, 0≤w≤0.8, 0≤ω≤0.8. According to the present invention, the Li 7- i A i La 3-j A' j Zr 2-q A” q O 12+δ Having a garnet structure; the Li u J v La 2-w J' w O 4+ω It has a layered perovskite structure, and the two form an ionic and electronic conductive network, which can not only inhibit the side reaction between the multi-electrode positive electrode material and the electrolyte to improve the stability of the multi-electrode positive electrode material in the battery cycle, but also improve the lithium ion transmission at the interface between the positive electrode and the electrolyte, and improve the rate performance of the multi-electrode positive electrode material. At the same time, the stable crystal structure of the coating layer itself can also inhibit the increase of impedance during the cycle, thereby improving battery performance.
[0038] According to the present invention, the average particle size D of the multi-element positive electrode material is 50 2-30 μm; preferably 3-20 μm.
[0039] According to the present invention, the thickness of the fast ion conductor coating layer is 2-30 nm, preferably 3-15 nm.
[0040] According to the present invention, the mass ratio of the fast ion conductor coating layer to the substrate is (0.01-5):100, preferably, the mass ratio is (0.05-1):100.
[0041] A second aspect of the present invention provides a method for preparing a multi-element positive electrode material, wherein the preparation method comprises:
[0042] (1) preparing a mixed salt solution of cobalt salt, manganese salt and nickel salt according to the molar ratio of Ni:Co:Mn=(1-xy):x:y;
[0043] (2) contacting the mixed salt solution, the salt solution of the M source, the precipitant solution and the complexing agent solution to perform a coprecipitation reaction to obtain a solid-liquid mixed slurry; and then filtering, washing, drying and sieving the solid-liquid mixed slurry to obtain a multi-element positive electrode material precursor;
[0044] (3) mixing, sintering, crushing and screening the multi-element material precursor, the lithium source and the M' source compound to obtain a multi-element positive electrode material matrix;
[0045] (4) Using the first process: Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , Li u J v La 2-w J' w O 4+ω Mixing with the multi-element positive electrode material matrix, and subjecting to first sintering, crushing, and screening, to obtain a multi-element positive electrode material coated with a fast ion conductor;
[0046] or,
[0047] The second process: Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , lanthanum source, J source compound, J' source compound, lithium salt and the multi-element positive electrode material matrix are mixed, and after a second sintering, crushing and screening, a multi-element positive electrode material coated with a fast ion conductor is obtained.
[0048] According to the present invention, the nickel salt, the cobalt salt and the manganese salt are each independently selected from at least one of sulfate, nitrate, chloride, oxalate, acetate and citrate.
[0049] Furthermore, the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate, nickel acetate and nickel citrate; the cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate, cobalt acetate and cobalt citrate; the manganese salt is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate, manganese acetate and manganese citrate.
[0050] According to the present invention, the precipitant solution may be a conventional precipitant solution in the art, for example, the precipitant solution is a sodium hydroxide solution.
[0051] According to the present invention, the complexing agent solution may be a conventional complexing agent solution in the art, for example, the complexing agent solution is an aqueous ammonia solution.
[0052] According to the present invention, in step (1), the concentration of the mixed salt solution is 1-3 mol / L, the concentration of the precipitant solution is 1-15 mol / L, the concentration of the complexing agent solution is 1-15 mol / L, and the concentration of the M source salt solution is 0.01-1 mol / L.
[0053] The usage of the precipitant solution and the complexing agent solution is not particularly limited and can be controlled according to the morphology and particle size of the prepared multi-element positive electrode material precursor.
[0054] Furthermore, the concentration of the mixed salt solution is 1.5-2.5 mol / L, the concentration of the precipitant solution is 5-10 mol / L, the concentration of the complexing agent solution is 5-10 mol / L, and the concentration of the M source salt solution is 0.05-0.5 mol / L.
[0055] According to the present invention, the amount of the M source is such that 0<[n(M)] / [n(Ni)+n(Co)+n(Mn)]≤0.1.
[0056] In the present invention, when the amount of the M source meets the above range, the M element can effectively enter the lattice of the multi-element positive electrode material precursor, achieving doping of the positive electrode material precursor lattice at the molecular / ionic scale, while not causing serious lattice distortion to destroy structural stability and hinder lithium ion transmission.
[0057] Furthermore, the amount of the M source is such that 0.001≤[n(M)] / [n(Ni)+n(Co)+n(Mn)]≤0.05.
[0058] According to the present invention, the compounds of the M source and the M' source are selected from compounds of at least one element among Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B.
[0059] In the present invention, the M source and the M' source may be the same or different.
[0060] Furthermore, the salt solution of the M source is a water-soluble salt of the M source, preferably selected from at least one of sodium aluminate, barium nitrate, zirconium nitrate, zirconium chloride, titanium sulfate, niobium nitrate, tantalum nitrate, gallium nitrate, yttrium nitrate, ammonium tungstate, calcium chloride, lanthanum nitrate, cerium nitrate, magnesium nitrate and sodium borate.
[0061] Furthermore, the compound of the M' source is selected from at least one of an oxide of the M' source, a hydroxide of the M' source and a carbonate of the M' source.
[0062] According to the present invention, the particle size D of the multi-element positive electrode material precursor is 50 1-30 μm, preferably 3-20 μm.
[0063] According to the present invention, in step (2), the conditions of the coprecipitation reaction include: pH value of 10-13, reaction temperature of 40-70° C., and reaction time of 5-20 h.
[0064] Furthermore, the conditions of the coprecipitation reaction include: pH value of 11-12, reaction temperature of 50-60° C., and reaction time of 8-16 h.
[0065] According to the present invention, in step (3), the lithium source is added in an amount according to a molar ratio of 0.90≤n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)]≤1.30; further, the lithium source is added in an amount according to a molar ratio of 0.96≤[n(Li)] / [n(Ni)+n(Co)+n(Mn)+n(M)]≤1.08; when the amount of the lithium source meets the above range, a multi-element positive electrode material with a complete crystalline α-NaFeO2 structure can be formed, so that it has a higher specific capacity.
[0066] According to the present invention, the amount of the M' source is added according to a molar ratio of 0<n(M') / [n(Ni)+n(Co)+n(Mn)]≤0.1; further, the M' source is added according to a molar ratio of 0.001≤n(M') / [n(Ni)+n(Co)+n(Mn)]≤0.05. In the present invention, when the amounts of the M' source and the multinary positive electrode material precursor meet the above range, the M' element enters the multinary positive electrode material precursor lattice and / or grain boundary in the form of nano-groups, realizes doping at the nanoscale, and improves the stability of the crystal structure and the surface interface stability.
[0067] According to the present invention, in step (3), the expression of the multi-element positive electrode material matrix is Li z [(Ni 1-x- y Co x Mn y ) 1-α M α ] 1-β M' βO2; 0.9≤z≤1.3, 0.001≤x≤1, 0≤y≤1, 0<α≤0.1, 0<β≤0.1; preferably, 1.0≤z≤1.1, 0.001≤x≤0.5, 0≤y≤0.5, 0<α≤0.05, 0<β≤0.05.
[0068] According to the present invention, in step (4), if the first process is adopted, the Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ The dosage relationship satisfies the following mass ratio:
[0069] 0.1%≤m(Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ ) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5%.
[0070] The Li u J v La 2-w J' w O 4+ω The dosage relationship satisfies the following mass ratio:
[0071] 0.1%≤m(Li u J v La 2-w J' w O 4+ω ) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5%.
[0072] According to the present invention, in step (4), if the second process is adopted, the lithium salt is added in an amount according to a molar ratio of 0≤n(Li) / [n(J)+n(J')]≤2; the lanthanum source is added in an amount according to a molar ratio of 2≤n(La) / n(J)≤6; when the amount of the lithium source and the lanthanum source meets the above range, additional Li can be provided to form a layered perovskite structure. u J v La 2-w J' w O 4+ω Fast ion conductors, avoiding Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ The crystal structure is destroyed during the sintering process, which can make the prepared multi-element positive electrode material have a higher specific capacity. If there is a lot of lithium carbonate and lithium hydroxide remaining on the surface of the multi-element positive electrode material, especially the multi-element positive electrode material with a nickel content greater than 90%, lithium salt may not be added. Furthermore, the lithium source is added in an amount of 0≤n(Li) / [n(J)+n(J')]≤1 in a molar ratio.
[0073] The amount of the J source satisfies the following mass ratio:
[0074] 0.1%≤m(J source) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5%.
[0075] The amount of the J' source satisfies the following mass ratio:
[0076] 0.1%≤m(J'source) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5% is added.
[0077] In the present invention, when Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , Liu J v La 2-w J' w O 4+ω When the amounts of lanthanum source, J source and J' source meet the above range, the residual lithium carbonate and lithium hydroxide on the surface of the multi-material can be consumed, and garnet-structured Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and layered perovskite structured Li u J v La 2-w J' w O 4+ω The fast ion conductor coating layer facilitates the transmission of lithium ions in the coating layer, and can also inhibit the side reactions between the multi-electrode positive electrode material and the electrolyte, thereby improving the specific capacity, rate and cycle life of the multi-electrode positive electrode material.
[0078] According to the present invention, the lanthanum source compound is selected from at least one of lanthanum oxide, lanthanum hydroxide, lanthanum oxalate and lanthanum carbonate; the J source compound is selected from at least one of the oxide of the J source, the hydroxide of the J source and the carbonate of the J source; the J source is selected from a compound of at least one element of Al, Ni, Co, Cu and Fe.
[0079] According to the present invention, the J' source compound is selected from at least one of the oxides, hydroxides and carbonates of the J' source; the J' source is selected from a compound of at least one element selected from Ca, Ba, Sr, Y, Ce, Rb and Ru.
[0080] According to the present invention, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide and lithium nitrate.
[0081] According to the present invention, in step (4), the conditions of the first sintering and the second sintering are the same or different, and each includes: a sintering temperature of 650-1000°C, preferably 800-950°C; a sintering time of 4-20h, preferably 6-15h; in addition, in the first process, the sintering rate in the first sintering is 3-10°C / min, preferably 4-6°C / min; in the second process, the sintering rate in the second sintering is 0.5-2°C / min, preferably 0.8-1.5°C / min, so as to fully form a layered perovskite-type fast ion conductor.
[0082] According to the present invention, the M' source, Li 7-i A i La 3-j A' jZr 2-q A” q O 12+δ , Li u J v La 2-w J' w O 4+ω , J source, J' source D 50 Less than 200nm, specific surface area greater than 20m 2 / g.
[0083] In the present invention, D 50 Less than 200nm, surface area greater than 20m 2 / g of M' source, Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , Li u J v La 2-w J' w O 4+ω The compound of the J source and the J' source can make the M' source and the multi-element positive electrode material precursor mix uniformly. Preferably, the M' source, Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ , Li u J v La 2-w J' w O 4+ω Compound D with J source and J' source 50 10-150nm, specific surface area 50-500m 2 / g.
[0084] According to the present invention, the specific operations of filtering, washing, drying, mixing (mixing), grinding, crushing, screening, and iron removal are not particularly limited, as long as the requirements are met. In the present invention, the filtering can be achieved by suction filtration, filter pressing, centrifugation, etc.; drying can be achieved by hot air, infrared, microwave, etc.; the mixing can be achieved by a high-speed mixer, a V-type mixer, a double cone mixer, or a plow mixer; the grinding can be achieved by a stirring ball mill, a planetary ball mill, or a sand mill; the crushing can be achieved by roller crushing, a ball mill, an air flow mill, or a mechanical mill; the screening can be achieved by an ultrasonic vibrating screen; the iron removal can be achieved by an electromagnetic iron remover.
[0085] The third aspect of the present invention provides a multi-element positive electrode material prepared by the aforementioned preparation method.
[0086] A fourth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the aforementioned multi-element positive electrode material as a positive electrode material.
[0087] The present invention will be described in detail below through examples.
[0088] In the following examples and comparative examples:
[0089] The particle size of the multi-element cathode material precursor was measured using a Mastersizer 2000 laser particle size analyzer;
[0090] The coating layer components in the positive electrode material can be measured using a Rigaku X-ray diffractometer;
[0091] The thickness of the coating layer in the positive electrode material can be measured using a Hitachi HF5000 transmission electron microscope;
[0092] Raw materials such as nickel sulfate, cobalt sulfate, manganese sulfate and lithium hydroxide are commercially available products of battery grade unless otherwise specified.
[0093] Example 1
[0094] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0095] Step 1: Prepare a 2 mol / L mixed salt solution with a molar ratio of nickel sulfate, cobalt sulfate and manganese sulfate of 90:5:5. Prepare a 0.1 mol / L zirconium nitrate solution, a 2 mol / L NaOH solution and a 6 mol / L NH3·H2O complexing agent solution.
[0096] Step 2: Add the mixed salt solution, zirconium nitrate solution (M source), NaOH solution, and NH3·H2O complexing agent solution to the stirred reactor in parallel to react. Control the pH value of the reaction system to 11.2-11.8, and the temperature of the entire system to 60°C. 50 The reaction was stopped when the particle size reached 10 μm. The product was washed with water, filtered and dried to obtain a zirconium-doped multi-element positive electrode material precursor, wherein zirconium nitrate was added in an amount of Zr / (Ni+Co+Mn)=0.001 in a molar ratio.
[0097] Step 3: uniformly mix the zirconium-doped multi-element cathode material precursor, lanthanum hydroxide and lithium hydroxide in step 2, wherein lanthanum hydroxide D 50 =30nm, specific surface area is 100m 2 / g, lanthanum hydroxide (M' source) at a molar ratio of La / (Ni+Co+Mn) = 0.001, and lithium hydroxide at a molar ratio of Li / (Ni+Co+Mn+Zr+La) = 1.05. The mixture is then sintered at 850°C for 10 hours, and after crushing and screening, a zirconium-lanthanum doped multi-element positive electrode material matrix is obtained.
[0098] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La2Al 0.5 O4 is mixed evenly, among which Li 6.4 Al 0.2 La3Zr2O 12 D 50 =50nm, specific surface area is 120m 2 / g,Li 0.5 La2Al 0.5 O4D 50 =50nm, specific surface area is 100m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La2Al 0.5 The mass ratio of O4 is 1000:3.5:3.5. Then the mixture is heated to 600℃ at 5℃ / min and sintered for 10 hours. After crushing and screening, the multi-element positive electrode material A1 coated with a fast ion conductor is obtained. The composition is shown in Table 2. In addition to the characteristic peaks of the multi-element material, the XRD spectrum of A1 also contains Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 O4 characteristic peaks, such as Figure 1 shown.
[0099] Example 2
[0100] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0101] Step 1, step 2 and step 3 are the same as in Example 1.
[0102] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La 1.875 Sr0.125 Co 0.5 O4 is mixed evenly, among which Li 6.4 Al 0.2 La3Zr2O 12 D 50 =50nm, specific surface area is 120m 2 / g,Li 0.5 La 1.875 Sr 0.125 Co 0.5 O4D 50 =50nm, specific surface area is 150m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La 1.875 Sr 0.125 Co 0.5 The mass ratio of O4 is 1000:3.5:3.5. Then the mixture is heated to 600°C at 5°C / min and sintered for 10 hours. After crushing and screening, a multi-element positive electrode material A2 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0103] Example 3
[0104] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0105] Step 1, step 2 and step 3 are the same as in Example 1.
[0106] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , La2O3, Co(OH)2, and LiOH are mixed evenly, among which Li 6.4 Al 0.2 La3Zr2O 12 D 50 =50nm, specific surface area is 120m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of Co(OH)2 50 =30nm, specific surface area is 100m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12The mass ratio of La2O3, Co(OH)2 and LiOH is 1000:3.5:3.04:0.43:0.1. The mixture is then heated to 720°C at 1.5°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A3 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0107] Example 4
[0108] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0109] Step 1, step 2 and step 3 are the same as in Example 1.
[0110] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , La2O3, Al2O3, LiOH are mixed evenly, among which Li 6.4 Al 0.2 La3Zr2O 12 D 50 =50nm, specific surface area is 120m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of Al2O3 50 =20nm, specific surface area is 230m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 The mass ratio of La2O3, Al2O3 and LiOH is 1000:3.5:3.18:0.25:0.1. The mixture is then heated to 750°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A4 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0111] Example 5
[0112] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0113] Step 1, step 2 and step 3 are the same as in Example 1.
[0114] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.7 Ga 0.1 La 2.7 Sr 0.3 Zr2O 12 , Li 0.5 La2Al 0.5O4 is mixed evenly, among which Li 6.7 Ga 0.1 La 2.7 Sr 0.3 Zr2O 12 D 50 =25nm, specific surface area is 140m 2 / g,Li 0.5 La2Al 0.5 O4D 50 =50nm, specific surface area is 100m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.7 Ga 0.1 La 2.7 Sr 0.3 Zr2O 12 , Li 0.5 La2Al 0.5 The mass ratio of O4 is 1000:3.5:3.5. Then the mixture is heated to 450°C at 5°C / min and sintered for 10 hours. After crushing and screening, a multi-element positive electrode material A5 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0115] Example 6
[0116] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0117] Step 1: Prepare a 2 mol / L mixed salt solution with a molar ratio of nickel sulfate, cobalt sulfate and manganese sulfate of 60:10:30. Prepare 0.1 mol / L zirconium nitrate solution, 2 mol / L NaOH solution and 6 mol / L NH3·H2O complexing agent solution.
[0118] Step 2: Add the mixed salt solution, zirconium nitrate solution (M source), NaOH solution, and NH3·H2O complexing agent solution to the stirred reactor in parallel to react. Control the pH value of the reaction system to 11.2-11.8, and the temperature of the entire system to 60°C. 50 The reaction was stopped when the particle size reached 5 μm. The product was washed with water, filtered and dried to obtain a zirconium-doped multi-element positive electrode material precursor, wherein zirconium nitrate was added in an amount of Zr / (Ni+Co+Mn)=0.001 in a molar ratio.
[0119] Step 3: uniformly mix the zirconium-doped multi-element cathode material precursor, lanthanum hydroxide and lithium hydroxide in step 2, wherein lanthanum hydroxide D 50 =30nm, specific surface area is 100m 2 / g, lanthanum hydroxide (M' source) at a molar ratio of La / (Ni+Co+Mn) = 0.001, and lithium hydroxide at a molar ratio of Li / (Ni+Co+Mn+Zr+La) = 1.05. The mixture is then sintered at 880°C for 10 hours, and after crushing and screening, a zirconium-lanthanum doped multi-element positive electrode material matrix is obtained.
[0120] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.5 Al 0.1 LqCy 1.8 Nb 0.2 O 12 , La2O3, Co(OH)2, and LiOH are mixed evenly, among which Li 6.5 Al 0.1 LqCy 1.8 Nb 0.2 O 12 D 50 =45nm, specific surface area is 130m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of Co(OH)2 50 =30nm, specific surface area is 100m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.5 Al 0.1 LqCy 1.8 Nb 0.2 O 12 The mass ratio of La2O3, Co(OH)2 and LiOH is 1000:3.5:3.04:0.43:0.15. The mixture is then heated to 720°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A6 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0121] Example 7
[0122] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0123] Step 1, step 2 and step 3 are the same as in Example 5.
[0124] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.7 Ga 0.1 La 2.7 Sr 0.3 Zr2O 12 , La2O3, Al2O3, LiOH are mixed evenly, among which Li 6.7 Ga 0.1 La2.7 Sr 0.3 Zr2O 12 D 50 =25nm, specific surface area is 140m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of Al2O3 50 =20nm, specific surface area is 230m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.7 Ga 0.1 La 2.7 Sr 0.3 Zr2O 12 The mass ratio of La2O3, Al2O3 and LiOH is 1000:3.5:3.18:0.25:0.15. The mixture is then heated to 695°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A7 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0125] Example 8
[0126] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0127] Step 1, step 2 and step 3 are the same as in Example 5.
[0128] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Ga 0.2 Ln3Z 1.8 Co 0.2 O 12 , La2O3, CuO, LiOH are mixed evenly, among which Li 6.4 Ga 0.2 Ln3Z 1.8 Co 0.2 O 12 D 50 =30nm, specific surface area is 130m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of CuO 50 =20nm, specific surface area is 200m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Ga 0.2 Ln3Z 1.8 Co 0.2 O 12The mass ratio of La2O3, CuO and LiOH is 1000:3.5:3.02:0.37:0.11. The mixture is then heated to 720°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A8 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0129] Example 9
[0130] This embodiment is intended to illustrate the positive electrode material prepared by the method of the present invention.
[0131] Step 1, step 2 and step 3 are the same as in Example 5.
[0132] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Ga 0.2 LqCy 1.8 Ti 0.2 O 12 , La2O3, Fe2O3, LiOH are mixed evenly, among which Li 6.4 Ga 0.2 LqCy 1.8 Ti 0.2 O 12 D 50 =30nm, specific surface area is 130m 2 / g, D of La2O3 50 =20nm, specific surface area is 160m 2 / g, D of Fe2O3 50 =20nm, specific surface area is 230m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Ga 0.2 LqCy 1.8 Ti 0.2 O 12 The mass ratio of La2O3, Fe2O3 and LiOH is 1000:3.5:3.02:0.43:0.11. The mixture is then heated to 715°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material A9 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0133] Comparative Example 1
[0134] Step 1: Prepare a 2 mol / L mixed salt solution with a molar ratio of nickel sulfate, cobalt sulfate and manganese sulfate of 90:5:5. Prepare a 2 mol / L NaOH solution and a 6 mol / L NH3·H2O complexing agent solution.
[0135] Step 2: Add the mixed salt solution, NaOH solution and NH3·H2O complexing agent solution to the stirred reactor in parallel to react. Control the pH value of the reaction system to 11.2-11.8 and the temperature of the whole system to 60°C. 50 The reaction was stopped when the particle size reached 10 μm. The product was washed with water, filtered and dried to obtain a multi-element cathode material precursor.
[0136] Step 3: Evenly mix the multi-element positive electrode material precursor in step 2 with lithium hydroxide, wherein the lithium hydroxide is mixed at a molar ratio of Li / (Ni+Co+Mn)=1.05. Then, the mixture is sintered at 850°C for 10 hours, and after crushing and screening, the multi-element positive electrode material D1 is obtained. The composition of the multi-element positive electrode material D1 is shown in Table 2; the XRD spectrum of D1 only contains characteristic peaks of the multi-element material, such as Figure 1 shown.
[0137] Comparative Example 2
[0138] Step 1, step 2 and step 3 are the same as in Example 1.
[0139] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 0.5 La2Al 0.5 O4 is mixed evenly, among which Li 0.5 La2Al 0.5 O4D 50 =50nm, specific surface area is 100m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 0.5 La2Al 0.5 The mass ratio of O4 is 1000: 7. Then the mixture is heated to 720°C at 5°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material D2 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0140] Comparative Example 3
[0141] Step 1, step 2 and step 3 are the same as in Example 1.
[0142] Step 4: doping zirconium and lanthanum with a multi-element cathode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 Mix well, among which Li 6.4 Al 0.2 La3Zr2O 12 D 50 =50nm, specific surface area is 120m 2 / g, zirconium and lanthanum doped multi-element cathode material matrix, Li 6.4 Al 0.2La3Zr2O 12 The mass ratio is 1000:7. The mixture is then heated to 720°C at 1°C / min and sintered for 8 hours. After crushing and screening, a multi-element positive electrode material D3 coated with a fast ion conductor is obtained, and its composition is shown in Table 2.
[0143] Comparative Example 4
[0144] The multi-element material D4 was prepared according to the method of Example 1, except that in step 4, the sintering temperature was 350°C, the sintering time was 8 hours, and the heating rate was 5°C / min. The composition is shown in Table 2. The XRD spectrum of D4 contains characteristic peaks of multi-element materials and Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 O4 characteristic peaks, such as Figure 1 As shown, the peak intensity ratio and peak area ratio are not within the scope of the present invention.
[0145] Comparative Example 5
[0146] The multi-element material D4 was prepared according to the method of Example 1, except that in step 4, the zirconium-lanthanum-doped multi-element positive electrode material matrix, Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La2Al 0.5 The mass ratio of O4 is 1000:0.5:0.5, and its composition is shown in Table 2.
[0147] Table 2
[0148]
[0149] Test Example 1
[0150] The positive electrode materials prepared in the embodiment and the comparative example are used to assemble a liquid lithium-ion battery, and the specific steps are as follows: the positive electrode material, acetylene black and polyvinylidene fluoride are dispersed in an appropriate amount of NMP according to a mass ratio of 95:2.5:2.5, coated on an aluminum foil and dried, and then cut into a positive electrode sheet with a diameter of 12 mm, and then the positive electrode sheet is vacuum dried at 120°C for 12 hours and then vacuum sealed for storage. The negative electrode uses a lithium metal sheet with a diameter of 16 mm and a thickness of 1 mm; the diaphragm is a Celgard porous membrane with a thickness of 25 μm; the electrolyte uses LiPF6 as a solute, and equal volumes of ethylene carbonate, dimethyl carbonate and diethyl carbonate as solvents, and the concentration of LiPF6 is 1 mol / L.
[0151] The positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into a 2025 button cell in an argon-filled glove box with a water content and an oxygen content of less than 5ppm. The electrochemical performance of the liquid lithium-ion battery was tested, and the specific test included: keeping the test temperature at 25°C. Charge to 4.3V with a 0.1C charging current on the charge and discharge tester, switch to constant voltage charging until the charging current is ≤0.01C, and then discharge to 3V with a 0.1 discharge current, forming 2 cycles, and then repeat the 1C current for charging and discharging. Investigate the charge and discharge capacity and cycle performance of the positive electrode material in the liquid lithium-ion battery. The test results are shown in Table 3.
[0152] Table 3
[0153]
[0154] It can be seen from Table 2-Table 3 that:
[0155] The multi-element positive electrode material having Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and Li u J v La 2-w J' w O 4+ω Characteristic peaks, and Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ Peak intensity I of (422) crystal plane (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β The peak intensity of O2(003) crystal plane I (422) The ratio is 0.01%<I (422) / I (003) <1.2%;Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ (422) peak area A (422) With Liz [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β The peak area A of the O2(003) crystal plane (003) The ratio is 0.01%<A (422) / A (003) <1.2%;Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ Peak intensity I of (422) crystal plane (422) With Li u J v La 2-w J' w O 4+ω Peak intensity I of (103) crystal plane (103) The ratio is 0.2<I (422 / I (103) <1.5;Li 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ (422) peak area A (422) With Li u J v La 2-w J' w O 4+ω Peak area A of (103) crystal face (103) The ratio is 1.0<A (422 / A (103) <5.0. Li is not introduced 7-i A i La 3-j A' j Zr 2-q A” q O 12+δ and Li u J v La 2-w J' w O 4+ω Comparative Example 1 of the coating layer: Only Li is introduced u J v La 2-w J' w O 4+ω Comparative Example 2 of the coating layer and the introduction of only Li7-i A i La 3-j A' j Zr 2-q A” q O 12+δ The multi-component positive electrode material of comparative example 3 of the coating layer has higher discharge specific capacity, rate performance and cycle retention rate. It shows that the fast ion transmission channel constructed on the surface of the multi-component positive electrode material can increase the interface reaction rate between the positive electrode and the electrolyte, reduce the interface impedance, and improve the rate performance of the multi-component positive electrode material. At the same time, the stable crystal structure of the coating layer itself can also inhibit the increase of impedance during the cycle, thereby improving the battery performance.
[0156] Specifically, compared with Comparative Examples 2 and 3, by Li 6.4 Al 0.2 La3Zr2O 12 , Li 0.5 La2Al 0.5 O4 or cobalt hydroxide, lanthanum oxide, lithium hydroxide form Example 1, Example 2, Example 3, Example 4, and Example 5 with the characteristic structure of the present invention, which have higher discharge specific capacity, rate performance and cycle retention rate.
[0157] Specifically, compared with Comparative Example 4, the sintering temperature range of the present invention is limited by Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 Example 1 in which O4 is formed and has the characteristic structure of the present invention has higher discharge specific capacity, rate performance and cycle retention rate.
[0158] Furthermore, Example 1 which adopts the preferred heat treatment process of the present invention has a higher discharge specific capacity than Example 5 which does not adopt the preferred heat treatment process.
[0159] Furthermore, Example 1 using the preferred component ratio of the present invention has higher discharge specific capacity, rate performance and cycle performance than Comparative Example 5 not using the component ratio of the present invention.
[0160] Specifically, Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 The liquid lithium-ion battery assembled from the multi-electrode material A1 coated with an O4 fast ion conductor and the multi-electrode material D1 without coating has a 0.1C charge-discharge curve as shown in Figure 2 As shown. Figure 2It can be seen that the discharge specific capacities of the two in liquid lithium-ion batteries are 225.3mAh / g and 210.4mAh / g respectively, and the charge and discharge polarization of the former is lower than that of the latter.
[0161] By Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 The liquid lithium-ion battery assembled from the multi-electrode material A1 with an O4 fast ion conductor coating layer and the multi-electrode material D1 without coating has a cycle retention rate curve of both at 1C as shown in the figure. Figure 3 As shown. Figure 3 It can be seen that the cycle retention rate of the liquid lithium-ion battery with A1 as the positive electrode is higher than that of the liquid lithium-ion battery with D1 as the positive electrode, indicating that the coating layer can effectively avoid the side reaction between the positive electrode and the electrolyte, thereby improving the battery performance; and the discharge specific capacity of A1 at 1C is 202.1mAh / g, which is higher than the discharge specific capacity of D1 at 188.6mAh / g, indicating that the coating layer has good lithium ion conductivity characteristics.
[0162] Table 4 has Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 The capacity of multi-element cathode material A1 coated with O4 fast ion conductor in liquid lithium-ion battery system is higher than that of Li 0.5 La2Al 0.5 O4-coated multi-electrode material D2 and Li 6.4 Al 0.2 La3Zr2O 12 The coated multi-electrode material D3 shows that through reasonable fast ion conductor coating, an active coating layer with high ion / electron conductivity and stability to the electrolyte can be obtained, thereby improving the capacity and structural stability of the multi-electrode material.
[0163] Furthermore, in Example 4, the surface of the high nickel ternary material can form Li in situ 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 Ln2 0.5 O4 coating layer, indicating that the high nickel ternary material and Li 6.4 Al 0.2 La3Zr2O 12 reaction, that is, a higher nickel content can promote the formation of Li 0.5 Ln2 0.5 O4.
[0164] Test Example 2
[0165] The positive electrode materials prepared in the examples and comparative examples are used to assemble solid-state lithium-ion batteries, and the specific steps are as follows:
[0166] PEO and LiTFSI were kneaded in a mass ratio of 3:1 and then hot-pressed to form a film with a thickness of 30 μm. The electrolyte membrane was then cut into pieces with a diameter of 19 mm and vacuum dried at 60°C for 10 h before being vacuum-sealed for storage.
[0167] The positive electrode material, acetylene black, PVDF, and LiTFSI were dispersed in an appropriate amount of NMP in a mass ratio of 90:2:2:6, coated on aluminum foil and dried, and then cut into positive electrode sheets with a diameter of 12 mm. The positive electrode sheets were then vacuum dried at 120°C for 12 hours and then vacuum sealed for storage.
[0168] With metallic lithium as the negative electrode, the positive electrode sheet and the PEO electrolyte membrane were assembled into a 2025 button cell in a glove box filled with argon gas with a water content and an oxygen content of less than 5ppm. The electrochemical performance of the solid-state lithium-ion battery was tested, and the specific test included: maintaining the test temperature at 60°C. On the charge and discharge tester, it was charged to 4.2V at a charging current of 0.1C, switched to constant voltage charging until the charging current was ≤0.01C, and then discharged to 3V at a discharge current of 0.1, forming 2 cycles, and then repeated charging and discharging at a current of 0.2C. The charge and discharge capacity and cycle performance of the positive electrode material in the solid-state lithium-ion battery were investigated. The results are shown in Table 4.
[0169] Table 4
[0170]
[0171]
[0172] By Li 6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 Liquid lithium-ion battery assembled from multi-electrode material A1 with O4 fast ion conductor coating layer and multi-electrode material D1 without coating. Table 4 shows that the discharge specific capacities of the two in solid-state lithium batteries are 237.3 mAh / g and 220.4 mAh / g, respectively, and the charge and discharge polarization of the solid-state lithium-ion battery with A1 as the positive electrode is smaller than that of the solid-state lithium-ion battery with D1 as the positive electrode, indicating that the fast ion conductor coating layer can reduce the impedance between the positive electrode and the electrolyte, increase the electrochemical reaction rate at the interface between the positive electrode and the electrolyte, and improve the rate performance of the multi-electrode material. At the same time, the stable crystal structure of the coating layer itself can also inhibit the increase of impedance during the cycle, thereby improving the battery performance.
[0173] By Li6.4 Al 0.2 La3Zr2O 12 and Li 0.5 La2Al 0.5 The multi-element positive electrode material A1 coated with an O4 fast ion conductor and the multi-element positive electrode material D1 without coating are assembled into a solid-state lithium-ion battery. From Table 4, it can be seen that the cycle retention rates of the two at 0.2C are 78.3% and 47.7%, respectively. It can be seen that the cycle performance of the multi-element positive electrode material coated with a fast ion conductor is significantly better than that of the matrix, indicating that the coating layer can effectively avoid the side reaction between the positive electrode and the electrolyte, thereby improving the cycle retention rate of the battery.
[0174] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A multi-element positive electrode material, characterized in that: The multi-element positive electrode material comprises a substrate and a fast ion conductor coating layer coated on the surface of the substrate; the components of the fast ion conductor coating layer include Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ and Li u J v La 2-w J' w O 4+ω ; Among them, in the Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ A is selected from at least one of Al and Ga, A' is selected from at least one of Sr, Y and Ce, A'' is selected from at least one of Cu, Co, Ge, Hf, Ir, Mn, Mo, Ti, Ru, Se, Te, W, Sn, Sb, Nb and Ta, 0≤ i ≤2,0≤ j ≤1,0≤ q ≤2,0≤ δ ≤1, and i , j , k Different from 0 at the same time; Among them, in the Li u J v La 2-w J' w O 4+ω wherein J is selected from at least one of Al, Ni, Co, Mn, Cu and Fe, J' is selected from at least one of Ca, Ba, Sr, La, Y, Ce, Rb and Ru, and 0< u ≤1,0< v ≤1,0≤ w ≤1,0≤ ω ≤1; The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ Having a garnet structure; the Li u J v La 2-w J' w O 4+ω It has a layered perovskite structure; Among them, Li in the XRD of the multi-element positive electrode material 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ Peak intensity of (422) crystal plane I (422) With Li u J v La 2-w J' w O 4+ω Peak intensity of (103) crystal plane I (103) The ratio is 0.2<I (422 / I (103) <1.5; The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ (422) peak area A (422) With Li u J v La 2-w J' w O 4+ω Peak area A of (103) crystal plane (103) The ratio is 1.0<A (422) / A (103) <5.0; The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ Peak intensity of (422) crystal plane I (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β Peak intensity I of O2 (003) crystal plane (003) The ratio is 0.01%<I (422) / I (003) <1.2%; The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ (422) peak area A (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β Peak area A of O2 (003) crystal plane (003) The ratio is 0.01%<A (422) / A (003) <1.2%.
2. The multi-element positive electrode material according to claim 1, wherein: The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ Peak intensity of (422) crystal plane I (422) With Li u J v La 2-w J' w O 4+ω Peak intensity of (103) crystal plane I (103) The ratio is 0.5<I (422 / I (103) <1.2; And / or, Li in the XRD of the multi-element positive electrode material 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ (422) peak area A (422) With Li u J v La 2-w J' w O 4+ω Peak area A of (103) crystal plane (103) The ratio is 1.5<A (422) / A (103) <3.
0.
3. The multi-element positive electrode material according to claim 1, wherein: A is selected from Al and / or Ga, A' is selected from Sr and / or Ce; A'' is selected from at least one of Co, Ti, W, Nb and Ta; 0≤ i ≤1,0≤ j ≤0.5,0≤ q ≤1,0≤ δ ≤0.5; J is selected from at least one of Al, Ni, Co and Cu; J' is selected from at least one of Ba, Sr, Y and Ce, 0 < u ≤0.8,0< v ≤0.8,0≤ w ≤0.8,0≤ ω ≤0.
8.
4. The multi-element positive electrode material according to claim 1, wherein The composition of the matrix includes Li z [(Ni 1-x- y Co x Mn y ) 1-α M α ] 1-β M' β O2; Wherein, M and M' are each independently selected from at least one of Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B; 0.9≤ z ≤1.3, 0.001≤x≤1, 0≤y≤1, 0<α≤0.1, 0<β≤0.
1.
5. The multi-element positive electrode material according to claim 4, wherein: M and M' are each independently selected from at least one of Al, Ba, Zr, Ti, Nb, Y, W, Sr, Cr, Mo, La, Ce, Mg and B; 1.0≤ z ≤1.1, 0.001≤x≤0.5, 0≤y≤0.5, 0<α≤0.05, 0<β≤0.
05.
6. The multi-element positive electrode material according to claim 1, wherein: The Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ Peak intensity of (422) crystal plane I (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β Peak intensity I of O2 (003) crystal plane (003) The ratio is 0.1%<I (422) / I (003) <0.5%; And / or, Li in the XRD of the multi-element positive electrode material 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ (422) peak area A (422) With Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β Peak area A of O2 (003) crystal plane (003) The ratio is 0.1%<A (422 / A (003) <0.5%.
7. The multi-element positive electrode material according to any one of claims 1 to 6, wherein: The average particle size D of the multi-element positive electrode material 50 2-30μm; And / or, the thickness of the fast ion conductor coating layer is 2-30 nm; And / or, the mass ratio of the fast ion conductor coating layer to the substrate is (0.01-5):
100.
8. The multi-element positive electrode material according to claim 7, wherein: The average particle size D of the multi-element positive electrode material 50 3-20μm; And / or, the thickness of the fast ion conductor coating layer is 3-15 nm; And / or, the mass ratio of the fast ion conductor coating layer to the substrate is 0.05% to 1%.
9. A method for preparing a multi-element positive electrode material according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) Cobalt salt, manganese salt and nickel salt are mixed according to Ni:Co:Mn=(1- xy ): x : y Prepare a mixed salt solution in a molar ratio of (2) contacting the mixed salt solution, the salt solution of the M source, the precipitant solution and the complexing agent solution to perform a coprecipitation reaction to obtain a solid-liquid mixed slurry; and then filtering, washing, drying and sieving the solid-liquid mixed slurry to obtain a multi-element positive electrode material precursor; (3) mixing, sintering, crushing and screening the compound of the multi-material precursor, lithium source and M' source to obtain a multi-material positive electrode material matrix; (4) Using the first process: Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ , Li u J v La 2-w J' w O 4+ω Mixing with the multi-element positive electrode material matrix, and subjecting to first sintering, crushing, and screening, to obtain a multi-element positive electrode material coated with a fast ion conductor; or, The second process: Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ , lanthanum source, J source compound, J' source compound, lithium salt and the multi-element positive electrode material matrix are mixed, and the multi-element positive electrode material coated with a fast ion conductor is obtained through a second sintering, crushing and screening.
10. The preparation method according to claim 9, wherein: The concentration of the mixed salt solution is 1-3 mol / L, the concentration of the precipitant solution is 1-15 mol / L, the concentration of the complexing agent solution is 1-15 mol / L, and the concentration of the M source salt solution is 0.01-1 mol / L; and / or, the amount of the M source is such that 0<[n(M)] / [n(Ni)+n(Co)+n(Mn)]≤0.1; and / or, the compounds of the M source and the M' source are selected from compounds of at least one element selected from Al, Ba, Zr, Ti, Nb, Ta, Ga, Y, W, Ca, Sr, Sc, Cr, Mo, Hf, Si, Sm, V, La, Ce, Mg and B; And / or, the salt solution of the M source is a water-soluble salt of the M source.
11. The preparation method according to claim 10, wherein: The amount of the M source is such that 0.001≤[n(M)] / [n(Ni)+n(Co)+n(Mn)]≤0.05; And / or, the salt solution of the M source is selected from at least one of sodium aluminate, barium nitrate, zirconium nitrate, zirconium chloride, titanium sulfate, niobium nitrate, tantalum nitrate, gallium nitrate, yttrium nitrate, ammonium tungstate, calcium chloride, lanthanum nitrate, cerium nitrate, magnesium nitrate and sodium borate.
12. The preparation method according to claim 9, wherein: The particle size D of the multi-element positive electrode material precursor 50 1-30μm; And / or, in step (2), the conditions of the coprecipitation reaction include: pH value of 10-13, reaction temperature of 40-70° C., and reaction time of 5-20 h.
13. The preparation method according to claim 12, wherein: The particle size D of the multi-element positive electrode material precursor 50 3-20μm.
14. The preparation method according to claim 9, wherein: The lithium source is added in an amount according to a molar ratio of 0.90≤n(Li) / [n(Ni)+n(Co)+n(Mn)+n(M)]≤1.30; And / or, the M' source is added in an amount according to a molar ratio of 0<n(M') / [n(Ni)+n(Co)+n(Mn)]≤0.1; and / or, the compound of the M' source is selected from at least one of the oxide of the M' source, the hydroxide of the M' source and the carbonate of the M' source.
15. The preparation method according to claim 14, wherein: The amount of the M' source is such that 0.001≤n(M') / [n(Ni)+n(Co)+n(Mn)]≤0.
05.
16. The preparation method according to claim 9, wherein: In step (3), the expression of the multi-element positive electrode material matrix is Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2; 0.9≤ z ≤1.3, 0.001≤x≤1, 0≤y≤1, 0<α≤0.1, 0<β≤0.1; and / or, the Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ The amount of the mass ratio is 0.1% ≤ m(Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ ) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5% added; and / or, the Li u J v La 2-w J' w O 4+ω The amount of the mass ratio is 0.1% ≤ m(Li u J v La 2-w J' w O 4+ω ) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5% added; and / or, in step (4), the lithium salt is added in an amount according to a molar ratio of 0≤n(Li) / [n(J)+n(J')]≤2; and / or, the lanthanum source is added in an amount according to a molar ratio of 2≤n(La) / n(J)≤6; And / or, the amount of the J source is 0.1%≤m(J source) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5% added; And / or, the amount of the J' source is 0.1%≤m(J' source) / m{Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2}≤5% added; And / or, the J source is a compound of at least one element selected from Al, Ni, Co, Cu, and Fe; And / or, the compound of the J source is selected from at least one of an oxide of the J source, a hydroxide of the J source and a carbonate of the J source; and / or, the J' source is a compound of at least one element selected from Ca, Ba, Sr, Y, Ce, Rb, and Ru; And / or, the compound of the J' source is selected from at least one of an oxide of the J' source, a hydroxide of the J' source and a carbonate of the J' source.
17. The preparation method according to claim 16, wherein: The expression of the multi-element positive electrode material matrix is Li z [(Ni 1-x-y Co x Mn y ) 1-α M α ] 1-β M' β O2; 1.0≤ z ≤1.1,0.001≤x≤0.5,0≤y≤0.5,0<α≤0.05,0<β≤0.05。 18. The preparation method according to claim 9, wherein: In step (4), the conditions of the first sintering and the second sintering are the same or different, and each includes: a sintering temperature of 650-1000° C. and a sintering time of 4-20 h; And / or, the sintering heating rate in the first sintering is 3-10°C / min; And / or, the sintering heating rate in the second sintering is 0.5-2°C / min.
19. The preparation method according to claim 18, wherein: In step (4), the conditions of the first sintering and the second sintering are the same or different, and each includes: a sintering temperature of 800-950° C.; a sintering time of 6-15 hours; And / or, the sintering heating rate in the first sintering is 4-6°C / min; And / or, the sintering heating rate in the second sintering is 0.8-1.5°C / min.
20. The preparation method according to claim 9, wherein: The compound of the M' source, Li 7-3i A i La 3-j A' j Zr 2-q A'' q O 12+δ , Li u J v La 2-w J' w O 4+ω , the compound of the J source, the compound of the J' source D 50 Less than 200nm, specific surface area greater than 20m 2 / g.
21. The preparation method according to claim 20, wherein: D 50 10-150nm, specific surface area 50-500m 2 / g.
22. A lithium ion battery, characterized in that: The lithium-ion battery comprises the multi-element positive electrode material according to any one of claims 1 to 8 as a positive electrode material.
Citation Information
Patent Citations
High-energy-density multi-element positive electrode material and preparation method thereof
CN109461928A